Effects of adverse childhood experiences on university students' ability to lead healthy lives: an exploratory qualitative study in Lahore, Pakistan - Rabia Fatima; Javeria Saleem; Muhammad Ishaq; Humera Zaib Khan; Gul Mehar Javaid Bukhari; Mahwish Naz; Aneela Fatima; Gholamreza Abdi; Mukul Jain (BMC, 2024)
Abstract Background Adverse Childhood Experiences are a significant global public health concern as these experiences have adverse effects on all the health determinants. Methods The interpretive phenomenological research design was used to explore the implications of adverse childhood experiences on the adult life of university students. An interpretive thematic analysis method was employed to analyze this study. Results Five major themes emerged after a comprehensive review of the information obtained from the interviews with the ten selected participants. These were (1) Chronic health struggles (2) Mental health disorders (3) Emotional and social difficulties (4) Paranoia and distrust and (5) Academic and professional under-performance. Conclusion This study concludes that adverse childhood experiences have long-lasting negative effects on university students' health and behaviour, preventing them from leading healthy lives and excelling academically and professionally.